Markers of Anemia in Children with Type 1 Diabetes - Ewa Rusak; Anna Rotarska-Mizera; Piotr Adamczyk; Bogdan Mazur; Joanna Polanska; Agata Chobot (Journal of Diabetes Research)
Aim. The aim of the study was to assess markers of anemia in type 1 diabetes (T1D) children, compare them to results obtained in the control group, and estimate their relation to BMI SDS. Methods. 94 (59% ♀) T1D children without other autoimmune disorders, aged 12.5 ± 4.1 years, T1D duration: 4.2 ± 3.6 years, HbA1c 7.3 ± 1.5% (57 ± 12.6 mmol/mol). Sex- and age-matched controls (43 children). In all children, anthropometric measurements, the blood count, iron turnover parameters, and vitamin B12 concentration were taken. Results. T1DM children had significantly higher red cell distribution width (RDW) (13.6 versus 12.6%; p<0.001), hepcidin (0.25 versus 0.12 ng/ml; p<0.001), and vitamin B12 concentrations (459 versus 397 pg/ml; p<0.01) and lower TIBC (59.09 versus 68.15 μmol/l; p<0.001) than in the control group. Logistic regression revealed that RDW, TIBC (both p<0.001), and hepcidin (p<0.05) significantly differentiated both groups. In T1DM children, BMI SDS negatively correlated with vitamin B12 (p<0.01) concentration and mean corpuscular hemoglobin concentration (p<0.05) and positively with TIBC (p<0.01) and HbA1c (p<0.001). Conclusions. Patients and controls differed especially in terms of RDW and TIBC. In studied T1DM children, BMI SDS was associated to iron metabolism parameters and vitamin B12 concentration.